Spectral Difference Interferometry for the Characterization of Optical Media. Issue 10 (26th August 2019) - Bottrill, Kyle R. H.; Ettabib, Mohamed A.; Demirtzioglou, Iosif; Marchetti, Riccardo; Lacava, Cosimo; Parmigiani, Francesca; Richardson, David J.; Petropoulos, Periklis
Abstract: A new form of interferometry combining high phase sensitivity and excellent mechanical isolation is proposed and demonstrated. These features arise from maintaining a probe and reference tone in the same medium under test at all times, their ultimate homodyne detection, as well as a novel method employing an optical programmable filter which is used to extract their relative phase difference. A compilation of studies performed to illustrate the applicability of the scheme to a range of measurements of optical propagation characteristics is presented. Measurements include the chromatic dispersion of SMF‐28 of lengths ranging from 1 m to 1 km, the nonlinear coefficient of highly nonlinear fiber and the phase transfer profile of an integrated optical ring resonator. Abstract : A new form of interferometry, spectral interferometry, is proposed, demonstrated, and characterized. By retaining the coherent probe and reference signals in the same medium at all times and ultimately interfering them through electro‐optic modulation, the scheme enables a high sensitivity homodyne measurement of the differential phase response of a medium to be made with high mechanical isolation and low complexity.